Laboratory Diagnosis of Brucellosis Using the Slide and Standard Tube Agglutination Methods - Yahya Faydi; Suleiman Al-Khalil (مجلة جامعة النجاح للأبحاث العلوم الطبيعية)
Both the rapid slide and standard tube agglutination methods were used for the diagnosis of 112 blood specimens for Brucellosis. We found that 56% of the patients have a titer < 1:20 while 33% have a titer > 1:80. We found that the rapid slide agglutination method correlates well with the tube agglutination method.